Effect of a Novel Pocket Compression Device on Hematomas Following Cardiac Electronic Device Implantation in Patients Receiving Direct Oral Anticoagulants - Fei, Ye-Ping; Wang, Lei; Zhu, Chun-Yan; Sun, Jing-Chao; Hu, Hui-Lin; Zhai, Chang-Lin; He, Chao-Jie (Frontiers in Cardiovascular Medicine, 2022)
Background A pocket hematoma is a well-recognized complication that occurs after pacemaker or defibrillator implantation. It is associated with increased pocket infection and hospital stay. Patients suffering from atrial fibrillation and undergoing cardiovascular electronic implantable device (CIED) surgery are widely prescribed and treated with direct oral anticoagulants (DOACs). In this study, the use of a novel compression device was evaluated to examine its ability to decrease the incidence of pocket hematomas following device implantation with uninterrupted DOACs. Methods A total of 204 participants who received DOACs and underwent CIED implantation were randomized into an experimental group (novel compression device) and a control group (elastic adhesive tape with a sandbag). The primary outcome was pocket hematoma, and the secondary outcomes were skin erosions and patient comfort score. Grade 3 hematoma was defined as a hematoma that required anticoagulation therapy interruption, re-operation, or prolonged hospital stay. Results The baseline characteristics of both groups had no significant differences. The incidence of grades 1 and 2 hematomas was significantly lower in the compression device group than in the conventional pressure dressing group (7.8 vs. 23.5 and 2.0 vs. 5.9%, respectively; P < 0.01). Grade 3 hematoma occurred in 2 of 102 patients in the experimental group and 7 of 102 patients in the control group (2.0 vs. 6.9%; P = 0.03). The incidence rates of skin erosion were significantly lower, and the patient comfort score was much higher in the compression device group than in the control group (P < 0.01). Multivariable logistic regression analysis showed that the use of novel compression device was a significant protective factor for pocket hematoma (OR = 0.42; 95% CI, 0.29–0.69, P = 0.01). Conclusions The incidence of pocket hematomas and skin erosions significantly decreases when the proposed compression device is used for patients undergoing device implantation with uninterrupted DOACs. Thus, the length of hospital stay and re-operation rate can be reduced, and patient comfort can be improved. Clinical Trial Registration http://www.chictr.org.cn, identifier: ChiCTR2100049430.